Дослідження особливостей формування кристалічної структури безперервнолитої заготовки під час примусового перемішування її рідкої серцевини - Смірнов, О.М.; Ухін, В.Є.; Верзілов, О.П. (Physico-technological Institute of Metals and Alloys, 2023)
The most effective method for studying the dynamics of solidification of various kinds of ingots is physical modeling. A physical model that simulates a cross section of a continuously cast billet was created. The results of physical modeling of the continuously cast billet solidification process with the forced stirring of its liquid core are presented. The features of the continuously cast billet crystal structure formation during the forced stirring of its liquid core with a magnetic field at different stages of solidification are shown. As a result of the experiments it was established, that during the forced stirring of the liquid core, when the melt flow interacts with the solidification front, the growth rate of the first order dendrite branches decreases by 50–90 %, and the growth rate of the second order branches increases compared to the calm state of the bath by 20–90 %. In this case, the highest values of increase in growth rate are observed in dendrites, the secondary branches of which grow in the direction opposite to the movement of fluid flow. The predominant development of second order branches of dendritic crystals in this case makes it possible to fill the volumes of liquid in the intercrystalline space and increase the density of the solid shell. It is shown, that the vertices of the columnar crystals protruding beyond the solidification front break off, dendrite fragments fall into a liquid bath, and the crystals themselves are deformed when colliding with moving equiaxial crystals. In this case, the front line of solidification is aligned, and the emerging crystal structure is compacted. The presence of particles of the solid phase before the solidification front in the columnar crystals growth zone, in turn, under certain conditions helps to accelerate the transition from the columnar crystals zone to the zone of equiaxial crystals.